Long-term use of mandibular advancement devices for the treatment of obstructive sleep apnea: A systematic review of craniofacial changes - Balanta-Melo, Julian (Revista Estomatología, 2014)
Objective: The aim of this study is to identify the craniofacial changes of long term use of Mandibular Advancement Devices (MAD) for Obstructive Sleep Apnea (OSA) treatment trough a systematic review of the literature. Materials and methods: A systematic review was performed assessing the following electronic databases: PubMed, EBSCOhost, The Cochrane Library and EMBASE,between January 2000 and May 2014, human studies and english language. Inclusion and exclusion criteria were applied to the results. Selected articles were evaluated with the use of an international check list related to the type of the study (CONSORT). A classification of the level of evidence and the degree of recommendation were performed trough the SORT strategy. Results: 1383 articles were identified after the initial search. After applying the criteria selection and complete the check list selected (CONSORT) only 1 study fulfilled the inclusion criteria. A classification of the level of evidence and grade of recommendation were performed by using the SORT strategy to the selected article. Conclusions: No enough body of evidence were found in this study to identify the craniofacial changes with the long term use of Mandibular Advancement Devices for the treatment of Obstructive Sleep Apnea.